2020
DOI: 10.3906/tar-1902-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cereal cyst nematode Heterodera filipjevi on wheat yields in Turkey

Abstract: The cereal cyst nematode Heterodera filipjevi (Madzhidov) Stelter is an important yield-limiting soil-borne pathogen of wheat-and barley-growing areas, particularly in the semiarid regions throughout the world. In Turkey, cyst nematodes have been detected in several localities of wheat-and barley-growing areas. This study was conducted to evaluate the effects of initial population densities (Pi) of Heterodera filipjevi on yield of susceptible (Seri-82) and resistant (Silverstar) wheat cultivars and to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Sahin et al (2008) reported that H. filipjevi was found infesting wheat fields in Haymana, Turkey where nematode population densities have reached (115 eggs and J2) per g soil. This may prove that H. filipjevi has great potential to cause damage and significant yield losses in wheat cultivation in Turkey and, this species caused yield loss in cultivars Seri-82 and Silverstar averaging 8.5% and 40.5% in two-year experiments (Imren et al, 2020), respectively. Fard et al (2018 conducted field experiments to investigate the impact of H. filipjevi on three wheat cultivars and their results showed significant reductions in grain yield in the range of 19.5% and 27.8%.…”
Section: Cereal Cyst Nematodes (Ccns)mentioning
confidence: 92%
See 1 more Smart Citation
“…Sahin et al (2008) reported that H. filipjevi was found infesting wheat fields in Haymana, Turkey where nematode population densities have reached (115 eggs and J2) per g soil. This may prove that H. filipjevi has great potential to cause damage and significant yield losses in wheat cultivation in Turkey and, this species caused yield loss in cultivars Seri-82 and Silverstar averaging 8.5% and 40.5% in two-year experiments (Imren et al, 2020), respectively. Fard et al (2018 conducted field experiments to investigate the impact of H. filipjevi on three wheat cultivars and their results showed significant reductions in grain yield in the range of 19.5% and 27.8%.…”
Section: Cereal Cyst Nematodes (Ccns)mentioning
confidence: 92%
“…The occurrence of P. thornei and P. neglectus in diverse wheat-growing fields in Jordan has been documented (Al-Banna et al, 2015). Pratylenchus thornei, P. neglectus, and P. scribneri have also been characterized from wheat producing provinces of Isparta in Turkey (Sogut & Devran, 2011;Imren et al, 2020). Pratylenchus neglectus, P. thornei, P. pseudopratensis and P. penetrans have been recorded in wheat-growing fields of Iran (Ghaderi et al, 2010) where P. thornei and P. neglectus were found prevalent (Pourjam et al, 1999).…”
Section: Root-lesion Nematodes (Rln)mentioning
confidence: 99%
“…CCNs nematodes alone are estimated to reduce the production of crops by 10% globally (Ali et al, 2019). Economic losses in cereals caused by CCNs were documented and reported in several studies around the world (Dababat and Fourie, 2018;İmren et al, 2019). Among the 80 valid species of the genus Heterodera Schmidt, 1871 (Subbotin et al, 2010b;Haque and Khan, 2021), the most common and economically important nematode species found associated with wheat is Heterodera avenae Wollenweber, 1924.…”
Section: Major Nematode Pests Of Wheatmentioning
confidence: 99%
“…is difficult and needs experienced scientists. Currently, molecular identification techniques are used overcome the taxonomic difficulties with morphological species identification (Dababat et al, 2015;Imren et al, 2020). Determination of the genetic variation in cyst nematode populations also aids the development or improvement of resistant host plants.…”
Section: Introductionmentioning
confidence: 99%